Enzymes and microorganisms jointly promote the fermentation of rapeseed cake - Song, Yujie; Sun, Litao; Zhang, Shuning; Fan, Kai; Wang, Huan; Shi, Yujie; Shen, Yaozong; Wang, Wenmei; Zhang, Jie; Han, Xiao; Mao, Yilin; Wang, Yu; et al. (Frontiers in Nutrition, 2022)
Rapeseed cake is a by-product of rapeseed oil separation. The nutritional components of rapeseed cake mainly include a variety of carbohydrates, proteins, and minerals. In order to improve the conversion rate of rapeseed cake, we studied the physicochemical properties, the structure of microbial communities, and the composition of metabolites in rapeseed cake after enzymatic fermentation. The results showed that the addition of enzymatic preparation increased microbial diversity. The relative abundance of Bacillus, Lysinibacillus, Empedobacter, Debaryomyces, Hyphopichia, and Komagataella in enzymatic fermentation was significantly higher than that in natural fermentation. Unlike natural fermentation, microbial diversity during enzymatic fermentation is specific, which improves the efficiency of fermentation. Otherwise, enzymatic fermentation promotes the conversion of macromolecular substances in rapeseed cake, which increases small metabolites, such as fatty acids, organic acids, amino acids and their derivatives. The metabolite enrichment pathway is mostly concentrated in sugar metabolism and fatty acid metabolism. In conclusion, after adding enzymatic preparation, enzymes and microorganisms jointly promote the transformation of macromolecules during the fermentation of rapeseed cake, which laid a good foundation for further utilization of rapeseed cake.